Comparative Techniques for Extraction of Ni, Cu, Zn and Pb in Guinea Corn Fields of Kaduna Metropolis, Nigeria - Ayodele J.T.; Mohammed S. S. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
The potential migration of metals in soil systems is dependent on the chemical form of the metal which is necessary for estimating its biological availability, physico-chemical reactivity and transport in the environment and into the food chain. Chemical extraction procedures are able to predict the changes in the heavy metal mobility or bioavailability in soils. In this study, the Ni, Cu, Zn and Pb concentrations of soil samples from guinea corn fields in Kaduna Metropolis were determined using Flame Atomic Absorption Spectrometry (FAAS). Hot and cold extraction techniques were employed for the digestion and extraction of the soil samples using 0.05mol/L EDTA, 1.0mol/L oxalic acid and 1.0mol/L acetic acid. The results indicated that there is no significant difference between hot and cold extraction techniques for these metals in these reagents except for Zn in 1.0mol/L Oxalic acid where there is a significant difference between hot and cold extraction and that the hot extraction is superior to the cold extraction with a mean of 6.37 against 1.41.